A thermodynamic evaluation of a multi-objective system optimized using integrated Pinch and exergy analysis - Ali Reza Hojjat; Mohammad Mehdi Keshtkar (Scientific Reports)
Abstract This article introduces an innovative multipurpose system that integrates a solar power plant with a coastal wind farm to generate refrigeration for refinery processes and industrial air conditioning. The system comprises multiple wind turbines, solar power plants, the Kalina cycle to provide partial energy for the absorption refrigeration cycle used in industrial air conditioning, and a compression refrigeration cycle for propane gas liquefaction. An extensive energy and exergy analysis was conducted on the proposed system, considering various thermodynamic parameters such as the solar power plant’s energy output, the absorption chiller’s cooling load, the electricity generated by the turbines, the wind turbines’ power output, and the energy efficiency and exergy of each cycle within the system. The analysis revealed that key factors like the inlet temperature of Terminal 66 as a heat transfer fluid for the solar power plant, the generator temperature of the absorption chiller, and the temperature and pressure at the Kalina cycle turbine inlet play a crucial role in influencing the solar power plant’s heat production, the absorption chiller’s cooling performance, and the turbines’ power output. The study concludes that the proposed multipurpose system can meet 22% of the refinery’s energy requirements. Additionally, to boost energy efficiency and minimize dependence on grid electricity, a combined Pinch and exergy analysis was employed on the liquefaction cycle. The findings show that optimizing the temperature levels of the refrigeration cycle’s evaporators can lead to a 22% reduction in power consumption. This approach has enabled the system to meet 29% of the refinery’s energy requirements.